The Role of Magnetoencephalography in the Early Stages of Alzheimer’s Disease - López-Sanz, David; Serrano, Noelia; Maestú, Fernando (Frontiers in Neuroscience, 2018)
The ever increasing proportion of aged people in modern societies is leading to a substantial increase in the number of people affected by dementia, and Alzheimer´s Disease in particular, which is the most common cause for dementia. Throughout the course of the last decades several different compounds have been tested to stop or slow disease progression with limited success, which is giving rise to a strong interest towards the early stages of the disease. Alzheimer´s disease has an extended an insidious preclinical stage in which brain pathology accumulates slowly until clinical symptoms are observable in prodromal stages and in dementia. For this reason, the scientific community is focusing into investigating early signs of AD which could lead to the development of validated biomarkers. While some CSF and PET biomarkers have already been introduced in the clinical practice, the use of non-invasive measures of brain function as early biomarkers is still under investigation. However, the electrophysiological mechanisms and the early functional alterations underlying preclinical Alzheimer´s Disease is still scarcely studied. This work aims to briefly review the most relevant findings in the field of electrophysiological brain changes as measured by magnetoencephalography (MEG). MEG has proven its utility in some clinical areas. However, although its clinical relevance in dementia is still limited, a growing number of studies highlight its sensitivity in this preclinical stages. Studies focusing on different analytical approaches will be reviewed. Furthermore, their potential applications to stablish early diagnosis and determine subsequent progression to dementia are discussed.